BD MAX Enteric Bacterial, Bacterial Plus, and Virus Panels for Diagnosis of Acute Infectious Gastroenteritis: a Cost-Benefit Analysis - Josep Ferrer; Estela Giménez; Diego Carretero; Javier Buesa; Francisco Morillas; Rafael Granell; Amadeo Fuenmayor; David Navarro; Eliseo Albert (Microbiology Spectrum, 2022)
ABSTRACT Economic assessment is required to gauge the value of implementing PCR syndromic platforms in the microbiology laboratory for the diagnosis of community-acquired acute gastroenteritis (AGE) in pediatric and adult in- and outpatients. A cost-benefit analysis was conducted from a health care system perspective using BD MAX Enteric Bacterial, Bacterial Plus, and Virus panels. Two 6-month periods were selected, in which either conventional procedures (in 2017) or BD MAX PCR multiplex panels (in 2018) were used. We retrospectively reviewed medical records of all patients with positive results and a representative sample of negative ones. A Markov model was used to represent transition probabilities between different health care states from time of stool microbiological study until completion of AGE-episode-associated health care. A total of 1,336 medical records were reviewed (829 in 2018 and 507 in 2017), showing overall a significantly higher positivity rate in 2018 than in 2017 (26% versus 6%, P < 0.001). The total cost per individual associated with health care for AGE was €314 in 2018 and €341 in 2017; when we only considered the pediatric cohort, the figures were €271 and €456, respectively. Using Tornado sensitivity analyses, we found that the three variables that most influenced the model in descending order of weight were the probability of longer hospital stays, the probability of returning to the emergency room (ER), and the probability of hospitalization from the ER. Use of BD MAX enteric PCR platforms for the diagnosis of community-acquired AGE instead of a non-PCR-based conventional approach results in an incremental benefit from a health care perspective in the general population, particularly children. IMPORTANCE The implementation of multiplex molecular panels allows microbiological laboratories to quickly, sensitively, and accurately diagnose acute infectious gastroenteritis. This methodology therefore allows faster decisions regarding treatment and infection control measures. Economic evaluations are required to gauge the value of implementing these syndromic PCR platforms in a community-based acute gastroenteritis setting. We studied the potential clinical and cost benefits, in terms of both their impact on laboratory costs and the subsequent costs of managing patients.